DETERMINATION OF THE ANTIOXIDANT ACTIVITY OF DIFFERENT TYPES OF COFFEE BY MEANS OF BRIGGS-RAUSCHER ANALYTICAL METHOD - SZABÓ, Gabriella; CSIKI, Emese; SZŐKE, Árpád Ferenc; MUNTEAN, Norbert (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The antioxidant activity of coffee brews was determined in batch conditions by means of a Briggs-Rauscher oscillating system. This method consists of the measurement of the inhibition time caused by the addition of a diluted coffee sample to the oscillating system. The inhibition time vs. the relative concentration of the diluted coffee sample shows linear dependence. The slope of these lines was used to calculate a relative antioxidant activity for each sample. It was concluded that the method of preparation greatly influenced the resulting coffee brew, with the filtering method showing the best results with up to 50% higher antioxidant activity. As such, it was chosen as a standard to compare activity values. It can also be noted that decaffeinated coffee samples show significantly lower activity than caffeine-containing ones.